Molecular and clinical characterization of hypervirulent Klebsiella pneumoniae isolates from individuals with urinary tract infections - Li, Jun; Tang, Mengli; Liu, Zhaojun; Xia, Fengjun; Min, Changhang; Hu, Yongmei; Wang, Haichen; Zou, Mingxiang (Frontiers in Cellular and Infection Microbiology, 2022)
Despite being a significant public health concern, hypervirulent Klebsiella pneumoniae (hvKP) has rarely been investigated in urinary tract infections (UTIs). To investigate the molecular and clinical characterization of hvKP in UTIs, we collected K. pneumoniae strains and clinical data from patients with UTIs. HvKP was confirmed by virulence-related genes and the Galleria mellonella model and sequenced by next-generation sequencing. Our data showed that 30/121 isolates were hvKP [17 carbapenem-resistant hypervirulent K. pneumoniae (CR-hvKP), 12 hvKP, and 1 extended-spectrum β-lactamase-producing hvKP]; these had higher resistance to most antimicrobials and were more likely to cause complicated UTIs (cUTIs). Notably, the mucoid phenotype-regulating genes prmpA and prmpA2 were truncated in 3 and 19 hvKP, respectively. Eight serotypes were detected and divided into three groups: K64 (n = 17), K1/K2 (n = 6), and others (n = 7). Furthermore, 16/17 K64 hvKP isolates were CR-hvKP but with a lower mortality rate of G. mellonella as the truncated prmpA/prmpA2 incurred high fitness cost to the isolates. In addition, all K64 isolates belonged to ST11 with the same cluster, and in two of these strains (KP88 and KP92) was successfully transferred blaKPC-2 gene to EC600. Genetic environment analysis showed that IS26–tnpR–ISKpn27–blaKPC−2–ISKpn6 may be the core structure in the horizontal transfer of blaKPC-2. The highest mortality rate among the infected G. mellonella was observed in the K1/K2 group. In conclusion, hvKP had a higher resistance rate and was more likely lead to cUTIs. Convergence of hypervirulence and carbapenem resistance in a transmissible ST11 clone of K64 K. pneumoniae was mediated by a plasmid in UTIs. Therefore, surveillance of hvKP in UTIs should be strengthened.